The Soviet Translation: Romanian Literary Translators after World War Two - Cotter, Sean (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis article describes the discourse and practice of translation during the Soviet colonization of Romania. Translation serves as an ideal object for the study of this cultural political process, because Soviet colonization emphasized the transformation of a nation through language. The new regime pursues a policy of foreignizing Romanian, creating the conditions for a resistant practice of domestication. This model reverses our common understanding of cultural politics of translation, exemplified by Lawrence Venuti. I focus on one actual translation: Lucian Blaga’s 1955 version of Faust. By looking at the role of translation in the Soviet colonization of Romania, we can better understand how culture, language, and power come together, creating unique forms of both domination and resistance.